2013
DOI: 10.1039/c3sm27643k
|View full text |Cite
|
Sign up to set email alerts
|

Droplet impact on superheated micro-structured surfaces

Abstract: When a droplet impacts upon a surface heated above the liquid's boiling point, the droplet either comes into contact with the surface and boils immediately (contact boiling), or is supported by a developing vapor layer and bounces back (film boiling, or Leidenfrost state). We study the transition between these characteristic behaviors and how it is affected by parameters such as impact velocity, surface temperature, and controlled roughness (i.e., micro-structures fabricated on silicon surfaces). In the film b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
163
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(190 citation statements)
references
References 30 publications
(49 reference statements)
15
163
3
1
Order By: Relevance
“…In the Leidenfrost regime, R w ¼ 0 during the whole spreading process, i.e., no wetting at all. Note that the present classification of the boiling regimes is based on the direct observation of wet respective dry areas, and is thus different from the classification in previous studies [8,11], where the boiling regimes were more superficially classified based on the smoothness of the droplet surface or the ejection of tiny droplets from the impacting droplet. On the basis of the definitions described above, the boiling regimes can be classified into contact, transition, and Leidenfrost for impact velocities ranging from about 0.5 to 4 m=s for both liquids.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…In the Leidenfrost regime, R w ¼ 0 during the whole spreading process, i.e., no wetting at all. Note that the present classification of the boiling regimes is based on the direct observation of wet respective dry areas, and is thus different from the classification in previous studies [8,11], where the boiling regimes were more superficially classified based on the smoothness of the droplet surface or the ejection of tiny droplets from the impacting droplet. On the basis of the definitions described above, the boiling regimes can be classified into contact, transition, and Leidenfrost for impact velocities ranging from about 0.5 to 4 m=s for both liquids.…”
mentioning
confidence: 67%
“…In order to determine the Leidenfrost temperature T L and its dependence on the impact velocity U, phase diagrams have been experimentally produced for various impacting droplets with many combinations of substrates and liquids: water on smooth silicon [8], water on microstructured silicon [11], FC-72 on carbon nanofiber [12], water on aluminium [13], and ethanol on sapphire [14]. All of these phase diagrams show a weakly increasing behavior of T L with U.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include splash [6][7][8][9][10], phase-change-induced surface levitation [11][12][13][14][15], skating on a film of trapped air [16][17][18], and rebounding [19][20][21][22]. Recently [11], it was demonstrated that drops can rebound after impact on an extremely cold solid carbon dioxide surface (at -79°C, well below the limit of even homogeneous nucleation of water), because of the formation of a sublimated vapor layer acting both as impact cushion and thermal insulator, enabling drops to hover and rebound without freezing.…”
Section: Introductionmentioning
confidence: 99%
“…Splashing is crucial in many important fields, such as the sprinkler irrigation and pesticide application in agriculture, ink-jet printing and plasma spraying in printing and coating industries, and spray cooling in various cooling systems; therefore its better understanding and effective control may make a far-reaching impact on our daily life. Starting in the 19th century, extensive studies on drop impact and splashing have covered a wide range of control parameters, including the impact velocity, drop size, surface tension, viscosity, and substrate properties (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and various splashing criteria have been proposed and debated (13)(14)(15)(16)(17)(18). Nevertheless, at the most fundamental level the generation mechanism of splashing remains a big mystery.…”
mentioning
confidence: 99%